Microstructure and thermal-mechanical evolution of high-entropy pyrochlore (A2B2O7) with dual crystalline phase - Kun Yang; Minghao Zhao; Huan Li; Chengying Bai (Open Ceramics)
Chemical complex solid solutions with dual-phases were successfully synthesized through solid-state reaction with its thermal-mechanical behavior subjected to proton irradiation were characterized. The dual-phase structural solid solutions demonstrate reduced thermal conductivity and enhanced mechanical performance, which can be associated with its chemical disorder and lattice distortion. Radiation hardening can be observed for the sample pellets with slight surface amorphization occurring, resulting in a Ti-enriched alteration layer covered on the surface.